2015
DOI: 10.1038/srep08796
|View full text |Cite
|
Sign up to set email alerts
|

FOXK2 Transcription Factor Suppresses ERα-positive Breast Cancer Cell Growth Through Down-Regulating the Stability of ERα via mechanism involving BRCA1/BARD1

Abstract: Estrogen receptors (ERs) are critical regulators of breast cancer development. Identification of molecules that regulate the function of ERs may facilitate the development of more effective breast cancer treatment strategies. In this study, we showed that the forkhead transcription factor FOXK2 interacted with ERα, and inhibited ERα-regulated transcriptional activities by enhancing the ubiquitin-mediated degradation of ERα. This process involved the interaction between FOXK2 and BRCA1/BARD1, the E3 ubiquitin l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 54 publications
3
55
2
Order By: Relevance
“…Moreover, the decreased FOXK2 mRNA levels predicted poor prognosis in patients with ccRCC, which was in accordance with the result of prognosis analysis on low FOXK2 expression in breast cancer. 18 Unlike previous studies, our results showed that in both FOXK2 knocked-down and overexpressed cells, no statistically significant changes were detected in the percentage of G0/G1 phases and S phase cells. We found that overexpression of FOXK2 inhibited the proliferation, migration and invasion of ccRCC cells, whereas knockdown of FOXK2 promoted these aspects.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Moreover, the decreased FOXK2 mRNA levels predicted poor prognosis in patients with ccRCC, which was in accordance with the result of prognosis analysis on low FOXK2 expression in breast cancer. 18 Unlike previous studies, our results showed that in both FOXK2 knocked-down and overexpressed cells, no statistically significant changes were detected in the percentage of G0/G1 phases and S phase cells. We found that overexpression of FOXK2 inhibited the proliferation, migration and invasion of ccRCC cells, whereas knockdown of FOXK2 promoted these aspects.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies on breast cancer illustrated that knockdown of FOXK2 led to a significant decrease in the percentage of G0/ G1 phase cells and a increase in the percentage of S phase cells; 17 whereas overexpression of FOXK2 decreased the percentage of S phase cells. 18 Unlike previous studies, our results showed that in both FOXK2 knocked-down and overexpressed cells, no statistically significant changes were detected in the percentage of G0/G1 phases and S phase cells. These results agree with our previous finding that FOXK2 mRNA level has no correlation with ccRCC tumor size, which imply that other potential mechanisms may be involved in the tumor-suppressive function of FOXK2.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…For further confirmation of the involvement of CCN5 in activation and functional response of ER-α in BC cells, we determined whether blocking CCN5 activity by CCN5-specific antibody treatment reduces the proliferative effect of E2 or impede the effect of 4OH-Tam (4-hydroxy-tamoxifen) on MCF-7 cells. Consistent with previous works, 13 , 43 , 44 , 45 , 46 E2 (10 n m ) treatment for 48 h, significantly increased MCF-7 cell viability, and this effect of E2 was significantly blocked when cells were pre-treated for 48 h with CCN5-antibody (CCN5 Ab ) followed by concomitant treatment with E2 and CCN5 Ab ( Figure 7a ). Moreover, CCN5 Ab treatment also reduced the cytotoxic effect of 4OH-Tam (10 μ m ) in these cells but was unable to reduce downright.…”
Section: Resultssupporting
confidence: 91%